2016
DOI: 10.1097/md.0000000000005181
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal tumors in children

Abstract: The use of minimally invasive surgery (MIS) in pediatric patients has been steadily increasing in recent years. However, its use for diagnosing and treating abdominal tumors in children is still limited compared with adults, especially when malignancy is a matter of debate. Here, we describe the experience at our center with pediatric abdominal tumors to show the safety and feasibility of MIS.Based on a retrospective review of patient records, we selected for study those pediatric patients who had undergone di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…In total, we report that the technique is feasible in 19% of tumors. This is comparable to previous reports of MIS for abdominal tumors in children 17,18 . We consider that it is still valuable in reducing long‐term morbidity, such as adhesion‐related complications 2 and presence of visible scars that alter quality of life 3 for almost 20% of patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In total, we report that the technique is feasible in 19% of tumors. This is comparable to previous reports of MIS for abdominal tumors in children 17,18 . We consider that it is still valuable in reducing long‐term morbidity, such as adhesion‐related complications 2 and presence of visible scars that alter quality of life 3 for almost 20% of patients.…”
Section: Discussionsupporting
confidence: 85%
“…This is comparable to previous reports of MIS for abdominal tumors in children. 17,18 We consider that it is still valuable in reducing long-term morbidity, such as adhesion-related complications 2 and presence of visible scars that alter quality of life 3 for almost 20% of patients. Additionally, as shown in the series, the larger the tumor, the higher the risk of conversion.…”
Section: -Year Efs 94%mentioning
confidence: 99%
“…In a similar study involving Iranian children with adnominal mass, Zareifar et al (22) (2016) reported comparable mean age of 4.8±4.2 years with similar higher proportion of males (1.9:1) and under 5 years age group (62.4%). A comparable mean age of 6.1±5.2 years has been reported by Oh et al (23) (2016) in Chinese children with abdominal mass while Solomon et al (24) (2017) observed similar higher proportion of under 5 years children in Ethiopia.…”
Section: Discussionsupporting
confidence: 80%
“…The range of MIS applications is now widening, from benign diseases to tumors, and studies on its use for malignant diseases are also being published. In 2016, Oh et al [21] reported that MIS is safe for the diagnosis and treatment of intraperitoneal tumors, including benign and malignant diseases. In particular, adrenalectomy and nephrectomy have been actively researched, [11,12,22,23,24,25,26] but there is no confirmed indication for MIS.…”
Section: Discussionmentioning
confidence: 99%